Methodological refinements in the behavior-analytic study of distraction: A preliminary investigation. Issue 1 (2nd January 2017) - Nosik, Melissa R.; Williams, W. Larry; Binder, Carl; Carr, James E.
ABSTRACT: Traditional approaches to the study of distraction have involved evaluations of the effect of a stimulus on specific task performance, but without a conceptual analysis of how the stimulus might actually interfere with the specific task. In the present study, we evaluated the potentially distracting effects of various classes of stimuli that were related to the task in different ways. We found that moderate-intensity stimuli that were topographically similar or were members of an equivalence class that included similar stimuli to the task (i.e., the discriminative stimulus and the target behavior) had the greatest distracting effects, high-intensity stimuli that were dissimilar had minor distracting effects and low-intensity stimuli that were dissimilar had negligible distracting effects.